Causal Inferences in Repetitive Transcranial Magnetic Stimulation Research: Challenges and Perspectives - Hobot, Justyna; Klincewicz, Michał; Sandberg, Kristian; Wierzchoń, Michał (Frontiers in Human Neuroscience, 2021)
Transcranial magnetic stimulation (TMS) is used to make inferences about relationships between brain areas and their functions because, in contrast to neuroimaging tools, it modulates neuronal activity. The central aim of this article is to critically evaluate to what extent it is possible to draw causal inferences from repetitive TMS (rTMS) data. To that end, we describe the logical limitations of inferences based on rTMS experiments. The presented analysis suggests that TMS alone does not provide the sort of premises that are sufficient to warrant strong inferences about causal properties of brain structures. Overcoming these limitations demands a close look at the designs of rTMS studies, especially the methodological and theoretical conditions which are necessary for functional decomposition of the relations between brain areas and cognitive functions. Some suggestions on how to manage some of these limitations are presented. We discuss the benefits of combining rTMS with neuroimaging in experimental reasoning and we address the restrictions and requirements of rTMS control conditions. We hope this summary and formalization of the reasoning behind rTMS research can be of use not only for scientists and clinicians who intend to interpret rTMS results in a causal manner but also for philosophers interested in causal inferences based on brain stimulation research.